Banking Entrepreneurial requirements: Models for selected countries: Models for selected countries (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to identify the requirements of banking Entrepreneurial in Saudi Arabia and Singapore, where banking Entrepreneurial is an important way to lead employees to acquire the experience and knowledge required by the banking environment, so we note the pursuit of the banking management to acquire new technology proactively and distinctively to compete with others through the introduction of modern technologies that help senior management to develop new banking methods adaptable to the surrounding environmental changes. The problem of research highlights the extent to which the requirements of banking Entrepreneurial are applied in Saudi Arabia and the Republic of Singapore and will be addressed through three investigations, the first research includes the theoretical aspect of the research, the second research is about analyzing the experiences of Saudi Arabia, the Republic of Singapore, and the third research analysis of data from Saudi Arabia, and Singapore in banking Entrepreneurial.